2012
DOI: 10.1016/j.drup.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy: A useful strategy to help combat multidrug resistance

Abstract: Multidrug resistance (MDR) renders cancer cells relatively invulnerable to treatment with many standard cytotoxic anti-cancer agents. Cancer immunotherapy could be an important adjunct other strategies to treat MDR positive cancers, as resistance to immunotherapy generally is unrelated to mechanisms of resistance to cytotoxic agents. Immunotherapy to combat MDR positive tumors could use any of the following strategies: direct immune attack against MDR positive cells, using MDR as an immune target to deliver cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 65 publications
1
28
0
1
Order By: Relevance
“…23 Mechanisms underlying chemotherapy-mediated upregulation of the anti-tumor immunity include upregulation of tumor cells immunogenicity, reduction of immune dysfunction by impairing the functionality of immunosuppressive cells, or induction of apoptotic cancer cell death, which activates immune responses. 129 It has been demonstrated that growing tumor cells can be much more sensitive to T-cell attack compared to the quiescent cells. 26 Therefore, chemotherapy could potentiate the efficiency of immunotherapy, at least in part, by stimulating compensatory tumor cell proliferation.…”
Section: Cryoablationmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Mechanisms underlying chemotherapy-mediated upregulation of the anti-tumor immunity include upregulation of tumor cells immunogenicity, reduction of immune dysfunction by impairing the functionality of immunosuppressive cells, or induction of apoptotic cancer cell death, which activates immune responses. 129 It has been demonstrated that growing tumor cells can be much more sensitive to T-cell attack compared to the quiescent cells. 26 Therefore, chemotherapy could potentiate the efficiency of immunotherapy, at least in part, by stimulating compensatory tumor cell proliferation.…”
Section: Cryoablationmentioning
confidence: 99%
“…For example, maximum tolerated doses of cyclophosphamide, doxorubicin or paclitaxel administered with an experimental cancer vaccine in a mouse model reduced vaccine efficacy, whereas the same doses given prior to vaccination improved vaccine efficacy. 129,131 Immunostimulating interventions often activate immunosuppressive feedback mechanisms, which prevent excessive immune responses. For example, on the one hand TLR agonists induce production of type I IFN and proinflammatory cytokines, such as IL-12, IL-1b, TNF-a and IL-6, but on the other hand these agents induce anti-inflammatory molecules, such as IL-10 and PGE2.…”
Section: Rational Immunotherapeutic Strategiesmentioning
confidence: 99%
“…These include cellular immunotherapy [119], whole call vaccines [120], multidrug resistance [121] and DCs [122]. Targeted therapeutic strategies along with ever improving designs in clinical trials pave the way for further success [123].…”
Section: Modes Of Immunotherapymentioning
confidence: 99%
“…Finally, immunotherapy could represent an important adjuvant to treat MDR, as resistance to immunotherapy generally is unrelated to the classical mechanisms of resistance to cytotoxic agents. Immunotherapy to combat MDR could consist of direct immune attack against MDR positive cells, using MDR as an immune target to deliver cytotoxic drugs, taking advantage of other immune properties of MDR positive cells or application of immunotoxins expressed under MDR control [498,499]. Regarding therapeutic approaches against drug resistance, nanodrug carriers, in particular liposomes, are widely explored [500][501][502].…”
Section: Tme Mediated Drug Resistancementioning
confidence: 99%